An Analysis of Security Competitions for a Beginner's Guide (Journal of The Colloquium for Information Systems Security Education, 2017)
Security competitions are emerging as a new approach in security education and professional training. At universities, security competitions are gradually introduced into Computer Science curriculum to attract more students into the security area and prepare them for a career in the security field. The benefits of competition-based education were recognized in many studies. However, there are still many challenges for beginners to participate in the competitions. To help beginners to study and participate, this paper analyzed thousands of competition problems in over a hundred security competitions in the past three years. This paper identifies several important characteristics of the security competitions, including the main security areas and the fundamental knowledge and skills to solve problems in these areas. This paper presents the findings as guidance to beginners so that they can find their interested areas to study and practice.
Keywords: Security Competition; Catch The Flag; Security Education; Competition Analysis; Competition Guide